Legal Protection of Incest Victims Who Have an Abortion - Achmad Prasetya Syailendra (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: Rape crime is a kind of violence against women in male sexual interests which show the position of vulnerable women. This gender-based violence is often caused by inequalities power in society or family. The annual report 2017 by the National Commission on Violence Against Women from sexual violence in private/personal sector, incest were the most reported cases as much as 1.210 cases. The incest case eventually spread to other criminal cases, for example, forced abortion by his family or the surrounding environment. The most detrimental impact of rape is pregnancy. Many rape victims can not bear the shame and disgrace; therefore, they prefer to stop their pregnancy or abortion even though abortion is illegal in Indonesia. That’s why legal protection of rape victim is needed, especially when the victim has an abortion.Purpose/Objective Study: This research aims to re-reflect the legality of abortion laws which regulated in Indonesian law. Furthermore, this research also reviewing legal protection for incest rape victims who are forced to have an abortion.Design/Methodology/Approach: This research is using a qualitative method with a normative judicial approach. The approach is carried out by examining library materials or secondary data as a basis for review, such as regulations and literature relating to the problem. The data is parsed in a descriptive narrative structured and coherent explanation.Findings: The rules regarding abortion in Indonesia are various, starting from those that are fully prohibited, to regulations which stated the exceptions. The rules are stated in the Criminal Code which fully prohibits abortion. While another rules legalizes the abortion for certain exceptions. Through these laws and regulations, Indonesia became a country which on the one hand absolutely prohibited abortion and on the other hand allowed abortion only for three cases, there are protecting the lives of mother, protecting fetus, and victim of rape. Abortion due to incest rape needs to be given forgiveness for the condition of the victim in charging the penalty. The psychological impact is more severe when keeping the baby because if the victim sees and raises the baby in a state of being unprepared and depressed it has bad consequences for the baby and the mother. When the victim sees the baby it will cause trauma, remembering the incident, thus will not treat the baby well and the baby’s growth and development will not good either.Paper Type: Research Article